Life cycle assessment of heated apron pavement system operations. (October 2016) - Shen, Weibin; Ceylan, Halil; Gopalakrishnan, Kasthurirangan; Kim, Sunghwan; Taylor, Peter C.; Rehmann, Chris R.
Highlights: Employed a hybrid Life Cycle Assessment (LCA) approach to evaluate energy and emissions from heated pavement (HPS) operations. One of the first studies to compare energy and emissions of airport HPS with those of traditional snow removal. Results can facilitate informed decision making by airport authorities on HPS implementation. Heating source efficiency and Coefficient of Performance (COP) of HPS are critical factors controlling energy and emissions. Abstract: Heated pavement systems (HPS) offer an attractive alternative to the cumbersome process of removing ice and snow from airport pavements using traditional snow removal systems. Although snow and ice removing efficiency and economic benefits of HPS have been assessed by previous studies, their environmental impact is not well known. Airport facilities offering public or private services need to evaluate the energy consumption and global warming potential of different types of snow and ice removal systems. Energy usage and emissions from the operations of hydronic heated pavement system using geothermal energy (HHPS-G), hydronic HPS using natural gas furnace (HHPS-NG), electrically heated pavement system (EHPS), and traditional snow and ice removal system (TSRS) are estimated and compared in this study using a hybrid life cycle assessment (LCA). Based on the system models assessed in this study, HPS application in the apron area seems to be a viable option from an energy or environmental perspective to achieve ice/snow free pavement surfaces without using mechanical or chemical methods. TSRS methods typically require more energy and they produce more greenhouse gas (GHG) emissions compared to HPS during the operation phase, under the conditions and assumptions considered in this study. Also, HPS operations require less energy and have less GHG emissions during a snow event with a smaller snowfall rate and a larger snow duration.